Descriptions of the eggs of some southern Australian Geometridae (Lepidoptera) - Young, Catherine J. (Zootaxa, 2006)
The eggs of 128 species in 67 genera of Australian Geometridae are described and illustrated using scanning electron micrographs and colour photographs. The Australian nacophorine eggs described in this study exemplified the diversity and heterogeneity of the group. On a wider scope, the egg characters of the Ennominae and Larentiinae also were found to be largely heterogeneous, in contrast to the relatively uniform egg characters of the Geometrinae, Oenochrominae s. str. and the Sterrhinae.